Injectable extracellular vesicle hydrogels with tunable viscoelasticity for depot vaccine - Rimsha Bhatta; Joonsu Han; Yusheng Liu; Yang Bo; Yueji Wang; Daniel Nguyen; Qian Chen; Hua Wang (Nature Communications)
Abstract Extracellular vesicles (EVs) have been actively explored for therapeutic applications in the context of cancer and other diseases. However, the poor tissue retention of EVs has limited the development of EV-based therapies. Here we report a facile approach to fabricating injectable EV hydrogels with tunable viscoelasticity and gelation temperature, by metabolically tagging EVs with azido groups and further crosslinking them with dibenzocyclooctyne-bearing polyethylene glycol via efficient click chemistry. One such EV gel has a gelation temperature of 39.4 °C, enabling in situ gelation of solution-form EVs upon injection into the body. The in situ formed gels are stable for over 4 weeks and can attract immune cells including dendritic cells over time in vivo. We further show that tumor EV hydrogels, upon subcutaneous injection, can serve as a long-term depot for EV-encased tumor antigens, providing an extended time for the modulation of dendritic cells and subsequent priming of tumor-specific CD8+ T cells. The tumor EV hydrogel also shows synergy with anti-PD-1 checkpoint blockade for tumor treatment, and is able to reprogram the tumor microenvironment. As a proof-of-concept, we also demonstrate that EV hydrogels can induce enhanced antibody responses than solution-form EVs over an extended time. Our study yields a facile and universal approach to fabricating injectable EV hydrogels with tunable mechanics and improving the therapeutic efficacy of EV-based therapies.